Pisang Ranggap: Pengetahuan lokal Masyarakat Sekitar Gunung Galunggung - Diana Hernawati; Rinaldi Rizal Putra; Ari Hardian; Asep Yudi Supriatna (Journal of Tropical Ethnobiology, 2021)
One of the biodiversity of bananas found in the Maluku Islands region is the sky barrel banana and is one of the locally endangered foods. However, the sky barrel is also found in the area of Mount Galunggung Tasikmalaya with the local name pisang ranggap. Therefore, the purpose of this research is to find out the indigenous knowlegde of galunggung community in contrast to its perception of pisang ranggap. Data collection is performed technically qualitatively descriptive in the form of in-depth interviews, literature studies, and field observations. The data sources in this study are indigenous people around Mount Galunggung as indigenous people. Based on the results of the study, it can be described that this banana was found before the eruption of 1982, can live on sandy soil. Pisang ranggap is believed to be an herbal remedy that has properties to treat back pain, kidney disorders, and diabetes. These results are reinforced by scientific knowledge that pisang ranggap is rich in beta carotene, riboflavin, flavonoids, niacin, alpha tocopherol, and vitamins A, B, C, E.